Exposure of married women to spousal violence: A community-based study in Eastern Turkey - Celebi, Evrim; Pirincci, Edibe; Durmus, Ayse Birsen (Turkish Assoc Trauma Emergency Surgery, 2022)
BACKGROUND: Violence against women deprives women of their rights to enjoy equality, security, dignity, self-worth and fundamental freedoms and devalues them; is one of the most significant social facts that force women to exist at a lower social level than men and constitute a significant obstacle to the formation of healthy societies. This study was conducted to determine the status of exposure to spousal violence of 15 years and older married women living in the city center. METHODS: Family health centers in Elazig Province were visited and 792 married women were selected from the related records by systematic sampling. As a data collection tool, a questionnaire form was used. The questionnaire consists of two parts. In the first part, participants were asked about demographic characteristics such as age, gender, education level, and profession, while in the second part, questions were asked to determine the extent of exposure to violence. Questionnaires were filled out using interview technique by making home visits. RESULTS: It has been found that the low level of education of the wife and her spouse, perception of the economic situation of the family as being bad, and the fact that the woman does not work in an income-generating business can be an important factor in exposing to both physical violence and economic violence by her husband. CONCLUSION: Conclusion: Rate of exposure to spousal violence is high in married women living in the city center of Elazig Province. Education and services should be provided for solving the problem at individual, familial, and social levels.
Evli kadınların eş şiddetine maruz kalma durumları: Türkiye’nin Doğusunda toplum tabanlı bir çalışma
Keywords: Economic violence; emotional violence; physical violence; sexual violence; spousal violence